PENERAPAN DAN EFEKTIVITAS UNDANG-UNDANG NOMOR II TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DITELAAH DARI SOSIOLOGI DAN BUDAYA INDONESIA - Poltak Siringoringo (to-ra, 2016)
The implementation and effectiveness of information legislation and electronic transactions are very weak, within the provisions of article 45, that the sanctions against the offenses were not optimal, because the law does not sanction a minimum, so that the law is legally vague and does not provide legal certainty, thus providing opportunities to abuse and misuse of information and communication technologies or misuse of electronic transactions by taking action so that the court can not apply the law, so it is not effective and is not optimal for violations and abuse of transaction information and communication. Keywords: electronic transactions,